2020
DOI: 10.29391/2020.99.008
|View full text |Cite
|
Sign up to set email alerts
|

Four Types of LME Cracks in RSW of Zn-Coated AHSS

Abstract: The thermal-mechanical-metallurgical characteristics of various crack locations are evaluated, and a classification of LME cracks is proposed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…Therefore, it can be concluded that the E/S contact significantly influences LME cracking during RSW. These observations are consistent with the findings reported in previous studies [11,20]; therefore, an attempt to investigate the role of Zn coatings on LME behaviour, as mentioned above, which has not been the focus of previous studies, is presented herein. Temperature distribution is an important factor for determining LME cracking in RSW; this can be inferred from the microstructure of the weldments, especially from the perspective of the fusion zone and heataffected zone (HAZ) [7,17].…”
Section: Lme Cracks In Weldssupporting
confidence: 91%
See 3 more Smart Citations
“…Therefore, it can be concluded that the E/S contact significantly influences LME cracking during RSW. These observations are consistent with the findings reported in previous studies [11,20]; therefore, an attempt to investigate the role of Zn coatings on LME behaviour, as mentioned above, which has not been the focus of previous studies, is presented herein. Temperature distribution is an important factor for determining LME cracking in RSW; this can be inferred from the microstructure of the weldments, especially from the perspective of the fusion zone and heataffected zone (HAZ) [7,17].…”
Section: Lme Cracks In Weldssupporting
confidence: 91%
“…Previous studies have found the temperature and stress distribution, and consequently, the LME cracking behaviour varies depending on the location of the electrode/sheet (E/S) interface [11, 20]. Therefore, an attempt was made to separate the locations of the E/S interface into various regions according to the contact behaviour between the electrode and the sheet, as presented in Figure 1(a–d).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this process is accompanied by a degradation of mechanical properties. This phenomenon is known as liquid metal embrittlement (LME) [2, 3]. Furthermore, LME poses an additional problem when the Zn-plated steel sheet is joined through resistance spot welding [4].…”
Section: Introductionmentioning
confidence: 99%